Comparing environmental impacts for livestock products: A review of life cycle assessments - de Vries, M.; de Boer, I.J.M. (Livestock science, 2010)
Livestock production has a major impact on the environment. Choosing a more environmentally-friendly livestock product in a diet can mitigate environmental impact. The objective of this research was to compare assessments of the environmental impact of livestock products. Twenty-five peer-reviewed studies were found that assessed the impact of production of pork, chicken, beef, milk, and eggs using life cycle analysis (LCA). Only 16 of these studies were reviewed, based on five criteria: study from an OECD (Organization for Economic Cooperation and Development) country, non-organic production, type of LCA methodology, allocation method used, and definition of system boundary. LCA results of these 16 studies were expressed in three ways: per kg product, per kg protein, and per kg of average daily intake of each product for an OECD country. The review yielded a consistent ranging of results for use of land and energy, and for climate change. No clear pattern was found, however, for eutrophication and acidification. Production of 1 kg of beef used most land and energy, and had highest global warming potential (GWP), followed by production of 1 kg of pork, chicken, eggs, and milk. Differences in environmental impact among pork, chicken, and beef can be explained mainly by 3 factors: differences in feed efficiency, differences in enteric CH 4 emission between monogastric animals and ruminants, and differences in reproduction rates. The impact of production of 1 kg of meat (pork, chicken, beef) was high compared with production of 1 kg of milk and eggs because of the relatively high water content of milk and eggs. Production of 1 kg of beef protein also had the highest impact, followed by pork protein, whereas chicken protein had the lowest impact. This result also explained why consumption of beef was responsible for the largest part of the land use and GWP in an average OECD diet. This review did not show consistent differences in environmental impact per kg protein in milk, pork, chicken and eggs. Only one study compared environmental impact of meat versus milk and eggs. Conclusions regarding impact of pork or chicken versus impact of milk or eggs require additional comparative studies and further harmonization of LCA methodology. Interpretation of current LCA results for livestock products, moreover, is hindered because results do not include environmental consequences of competition for land between humans and animals, and consequences of land-use changes. We recommend, therefore, to include these consequences in future LCAs of livestock products.